Kompetensi Guru Akidah Akhlak Dalam Mengelola Motivasi Belajar Siswa - Darrotul Jannah; Yoyoh Badriyah; Dede Majreha Djoharuddin (Oasis : Jurnal Ilmiah Kajian Islam, 2023)
AbstractThis study aims to determine the competence of teachers, student learning motivation, and the obstacle and support factors for Akidah Akhlak teacher competence in increasing student learning motivation at Madrasah Aliyah Tunas Cendekia Babakan Ciwaringin Cirebon. This study used a descriptive qualitative method with data collection techniques through observation, interviews and documentation review. From this study it can be concluded that Akidah Akhlak teachers at Madrasah Aliyah Tunas Cendekia do not apply social competence and professional competence but only apply pedagogic competence and personality competence. Teachers of Akidah Akhlak at Madrasah Aliyah Tunas Cendekia have not fully mastered teacher competence. By examining students' learning motivation at Madrasah Aliyah Tunas Cendekia, it found out that student learning motivation is still quite high. The obstacle of Akidah Akhlak teachers in increasing student learning motivation at Madrasah Aliyah Tunas Cendekia comes from Aqidah Akhlak teacher’s lackness of teacher competence, especially social and professional competence. Keywords:Teacher Competence, Student Learning Motivation, Students. AbstrakPenelitian ini bertujuan untuk mengetahui kompetensi guru, motivasi belajar siswa, dan faktor penghambat dan pendukung kompetensi guru Akidah Akhlak dalam meningkatkan motivasi belajar siswa di Madrasah Aliyah Tunas Cendekia Babakan Ciwaringin Cirebon. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi,wawancara dan tinjauan dokumentasi. Dari penelitian ini dapat disimpulkan bahwa guru Akidah Akhlak di Madrasah Aliyah Tunas Cendekia tidak mengaplikasikan kompetensi sosial dan kompetensi profesional melainkan hanya mengaplikasikan kompetensi pedagogik dan kompetensi kepribadian. Motivasi belajar siswa di Madrasah Aliyah Tunas Cendekia dalam kategori cukup tinggi. Penghambat kompetensi guru Akidah Akhlak dalam meningkatkan motivasi belajar siswa di Madrasah Aliyah Tunas Cendekia berasal dari guru Akidah Akhlak yang kurang menguasai kompetensi guru, lebih tepatnya kompetensi sosial dan profesionalnya. Kata Kunci:Kompetensi Guru, Motivasi Belajar Siswa, Siswa.